Effect of endometrial thickness on obstetric and neonatal outcomes in assisted reproduction: a systematic review and meta-analysis - Zheng Fang; Jialyu Huang; Jiaqin Mao; Lamei Yu; Xiaohong Wang (BMC, 2023)
Abstract Purpose This systematic review and meta-analysis aimed to explore the relationship of endometrial thickness (EMT) with obstetric and neonatal outcomes in assisted reproductive cycles. Methods PubMed, EMBASE, Cochrane Library and Web of Science were searched for eligible studies through April 2023. Obstetric outcomes include placenta previa, placental abruption, hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM) and cesarean section (CS). Neonatal outcomes include birthweight, low birth weight (LBW), gestational age (GA), preterm birth (PTB), small for gestational age (SGA) and large for gestational age (LGA). The effect size was estimated as odds ratio (OR) or mean difference (MD) with 95% confidence interval (CI) using a random-effects model. Inter-study heterogeneity was assessed by the chi-square homogeneity test. One-study removal method was used to determine the sensitivity of the meta-analysis. Results Nineteen studies involving 76,404 cycles were included. The pooled results revealed significant differences between the thin endometrium group and the normal group in placental abruption (OR = 2.45, 95% CI: 1.11-5.38, P = 0.03; I2 = 0%), HDP (OR = 1.72, 95% CI: 1.44-2.05, P < 0.0001; I2 = 0%), CS (OR = 1.33, 95% CI: 1.06-1.67, P = 0.01; I2 = 77%), GA (MD = -1.27 day, 95% CI: -2.41- -1.02, P = 0.03; I2 = 73%), PTB (OR = 1.56, 95% CI: 1.34-1.81, P < 0.0001; I2 = 33%), birthweight (MD = -78.88 g, 95% CI: -115.79- -41.98, P < 0.0001; I2 = 48%), LBW (OR = 1.84, 95% CI: 1.52-2.22, P < 0.00001; I2 = 3%) and SGA (OR = 1.41, 95% CI: 1.17-1.70, P = 0.0003; I2 = 15%). No statistical differences were found in placenta previa, GDM, and LGA. Conclusion Thin endometrium was associated with lower birthweight or GA and higher risks of placental abruption, HDP, CS, PTB, LBW and SGA. Therefore, these pregnancies need special attention and close follow-up by obstetricians. Due to the limited number of included studies, further studies are needed to confirm the results.